Effect of Multiple Jet Passes Treatment in Waterjet Peening on Fatigue Performance - Azmir, Azhari; Schindler, Christian; Godard, Claudia; Gibmeier, Jens; Kerscher, Eberhard (2015)
Waterjet technology started in early 1960s. Water is normally compressed up to about 600 MPa and discharged from a small orifice. Applications: machining, cleaning, coating removal, peening (WJP)etc.